2008
DOI: 10.1007/s00401-008-0372-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuropathological and genotypic variability in SNCA A53T familial Parkinson’s disease

Abstract: Individuals with familial Parkinson's disease (PD) due to a monogenic defect can show considerable clinical and neuropathological variability. To identify factors underlying this variability, histopathological analysis was performed in two clinically different A53T α-synuclein heterozygotes from Family H, a multigenerational α-synuclein A53T kindred. To determine whether additional genetic factors could contribute to phenotypic variability, Family H and another multigenerational A53T kindred were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 46 publications
11
57
0
Order By: Relevance
“…The clinical condition of our patient reveals a less aggressive phenotype than previously described in some family members from the Spanish study [15,22] (Table 1) and reinforces that marked phenotypic heterogeneity is common among patients with PD, even among those sharing the same mutation [27]. Although, overall, the reasons underlying the intra/interfamilial variability observed among PD patients with a-synuclein mutations are unknown, growing evidence suggest that genetic modifiers, influencing the disease expressivity, may account substantially for the observed clinical heterogeneity [27e29].…”
Section: Discussionsupporting
confidence: 86%
“…The clinical condition of our patient reveals a less aggressive phenotype than previously described in some family members from the Spanish study [15,22] (Table 1) and reinforces that marked phenotypic heterogeneity is common among patients with PD, even among those sharing the same mutation [27]. Although, overall, the reasons underlying the intra/interfamilial variability observed among PD patients with a-synuclein mutations are unknown, growing evidence suggest that genetic modifiers, influencing the disease expressivity, may account substantially for the observed clinical heterogeneity [27e29].…”
Section: Discussionsupporting
confidence: 86%
“…The patients in a family with E46K mutation had a cognitive deficit in the early stage of disease and DLB pathology; a high density of LBs was present not only in the subcortical nuclei but also in the parahippocampus, amygdala and cortex (Zarranz et al, 2004). The patients in families with the A30P or A53T mutation also exhibited diffuse LBs pathology (Markopoulou et al, 2008;Seidel et al, 2010). Although the widespread distribution of LBs formation in LBD with the E46K mutation (Zarranz et al, 2004) may be related to accelerated assembly of E46K αS observed in our study, it is difficult to correlate our in vitro results to clinicopathological findings reported in patients with these mutations.…”
Section: Discussionmentioning
confidence: 96%
“…The exact biological function of LRRK2 remains largely unclear and how its mutations lead to neurodegeneration is not known, but protein modifications from altered phosphorylation could lead to misfolding and aggregation of the target protein [278]. Therefore, increasing Three single point mutations in AS were found to be associated with EOPD: Ala53Thr (A53T), identified in a large Italian family (Contursi) [280] and in Greek kindreds [281][282][283][284], showing both AS and tau pathology [285], The A53T mutation was also found in diffuse DLB (DDLB) [286,287], while the relevance of DJ-1 mutation for DLB is not known. Ala30Pro (A30P), in a German kindred [288], shows similarities to PD but more severe pathology [289], and E46K or Glu46Lys [295].…”
Section: It Improves Mitochondrial Dysfunction Altersmentioning
confidence: 99%